Gamification-based Mobile Learning Development for Vocational High School Student Software Modeling Learning - Rifansah, Muhammad Ridho; Hidayat, Wahyu Nur Nur; Komariah, Kokom (Letters in Information Technology Education (LITE), 2023)
Generation Z tends to use mobile devices in their daily lives which can have a positive impact on the affective, cognitive, metacognitive, and socio-cultural development of students. In addition, most students direct their frustrations into playing games to make it more relaxed and fun. Currently, VHS in Indonesia, especially in the city of Malang, are intensively looking for alternative learning methods where students are active and enthusiastic in participating in the learning process due to the COVID-19 pandemic, so innovation is needed in learning. Based on observations and informal interviews and distributing questionnaires conducted at PVHS 12 Malang, VHS Nasional Malang, and PVHS 1 Kepanjen, motivation to learn software modeling subjects is still lacking. Currently, books and ppt are the main learning media used in the classroom. As a result, students lack the motivation to study the material independently. To overcome these problems, this research designs and develops mobile learning gamified and PBL. By applying the Systematic Education Design Cycle Iteration (ISDES) development model, the gamified & pbl mobile learning application is categorized as valid in terms of material suitability (95% validity score from material experts) and 94% of valid media suitability is reviewed by media experts. Meanwhile, the media reviewed in the small group were all valid: 84% in the small group test and 86% in the field test. The results showed that the results of the motivation test increased by 0.63% in the small-scale test & 0.56% in the large-scale test, both of which included a high increase in learning motivation. These results conclude that the media is valid and appropriate for student learning and increases learning motivation.